2014
DOI: 10.4209/aaqr.2013.03.0066
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Persistent Organic Pollutants and Male Reproductive Health

Abstract: Persistent organic pollutants (POPs) are chemicals that persist in the environment, bioaccumulate through the food chain, and exhibit toxic effects that threaten the health of humans and animals alike. The potential influence of POPrelated air pollution on male reproductive outcomes has attracted increasing interest in the scientific community and among policymakers and the public. Therefore, epidemiological studies on fertility should examine the impact of chronic exposure to POPs via inhalation. The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…They tend to accumulate in human bodies and have been detected in human milk and umbilical cord blood (Wang et al, 2008;Lin et al, 2011;Koh et al, 2010). Human with prenatal or postnatal exposure to PBDEs has been demonstrated to be associated with several adverse health outcomes (Chao et al, 2014b;Hsu et al, 2014) including low birth length and weight (Chao et al, 2007), menstrual irregularity , disruption of thyroid and growth hormones (Shy et al, 2012), and interference with neurological development in infants (Chao et al, 2011). In the recent study in the e-waste dismantling areas, the researchers found that serum levels of PBDEs were related with increasing levels of white blood cells, hemoglobin, and platelets (Xu et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…They tend to accumulate in human bodies and have been detected in human milk and umbilical cord blood (Wang et al, 2008;Lin et al, 2011;Koh et al, 2010). Human with prenatal or postnatal exposure to PBDEs has been demonstrated to be associated with several adverse health outcomes (Chao et al, 2014b;Hsu et al, 2014) including low birth length and weight (Chao et al, 2007), menstrual irregularity , disruption of thyroid and growth hormones (Shy et al, 2012), and interference with neurological development in infants (Chao et al, 2011). In the recent study in the e-waste dismantling areas, the researchers found that serum levels of PBDEs were related with increasing levels of white blood cells, hemoglobin, and platelets (Xu et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Toxicological data was achieved on the US EPA Integrated Risk Information System (IRIS) showing that reference doses for chronic oral exposure (RfDs) on neurobehavioral effects were 0.0001 (Benchmark Dose level (BMDL): 0.35 mg/kg), 0.0001 (BMDL: 0.29 mg/kg), 0.0002 (no-observe-adverse-effect level (NOAEL): 0.45 mg/kg) and 0.007 mg/kg/day (NOAEL: 2.22 mg/kg) in BDE-47, 99, 153, and 209, respectively (US EPA, 2008). PBDEs have continuously raised the public's and public officials' concern because of their ubiquity in the microenvironment and their association with several adverse health effects, including disruption of thyroid and growth hormone homeostasis, neurodevelopment, menstruation, pregnancy, and semen quality (Chao et al, 2007;Chao et al, 2010;Lin et al, 2011;Shy et al, 2012;Chao et al, 2014a;Hsu et al, 2014). Air levels of PBDEs are often lower outdoors than indoors .…”
Section: Introductionmentioning
confidence: 99%
“…To produce products using contaminated feeds or in contaminated fields will ultimately exert human health risks, especially to sensitive members of the population, such as infants and pregnant women. Various studies revealed that PTS play a crucial role in the pathogenesis of some health effects, such as POPs, Hg with male subfertility (Hauser et al, 2003;Hsu et al, 2014;McAuliffe et al, 2012), autism in children due to metal overload (Bjørklund, 2013;Hagmeyer et al, 2015); Cancers associated with high loadings of PTS in human bodies (Cohn et al, 2007;Li et al, 2011;Steinmaus et al, 2013;Vogt et al, 2012), etc.…”
Section: The Threats Of Environmental Pollutantsmentioning
confidence: 99%